Telepractice: A Survey of AuD Students Pre- and Post-Telepractice. - Watts, Kelli M.; Willis, Laura B. (Perspectives of the ASHA Special Interest Groups, 2017)
Telepractice, defined by the American Speech-Language-Hearing Association (ASHA, n.d.) as "the application of telecommunications technology to the delivery of professional services at a distance by linking clinician to client, or clinician to clinician, for assessment, intervention, and/or consultation," is a quickly growing aspect of practicing audiology. However, only 12% of audiologists are involved in providing services via telepractice (REDA International, Inc., 2002). Lack of knowledge regarding telepractice has been cited as one of the reasons many audiologists do not use telepractice to provide audiology services. This study surveyed audiology doctoral students regarding their opinions about the use of telepractice both before and after their opportunity to provide services via telepractice sessions. The authors expected that by providing students the opportunity to have hands-on training in telepractice with supervision, they would be more open to using telepractice after becoming licensed audiologists. Overall, the data indicates benefits of exposing students to telepractice while they are in graduate school.